A comparative study between a computer-based and a mobile-based assessment: Usability and user experience. Issue 4 (18th November 2019) - Nikou, Stavros A.; Economides, Anastasios A.
Abstract : Purpose: The purpose of this study is to compare the overall usability and user experience of desktop computers and mobile-devices when used in a summative assessment in the context of a higher education course. Design/methodology/approach: The study follows a between-groups design. The participants were 110 first-year undergraduate students from a European university. Students in the experimental group participated in the assessment using mobile devices, whereas students in the control group participated using desktop computers. After the assessment, students self-reported their experiences with computer-based assessment (CBA) and mobile-based assessment (MBA), respectively. The instruments used were the user experience questionnaire and the system usability scale. Findings: Attractiveness and novelty were reported significantly higher in the experimental group (MBA), while no significant differences were found between the two groups in terms of efficiency, perspicuity, dependability and stimulation. The overall score for the system usability was not found to differ between the two conditions. Practical implications: The usability and user experience issues discussed in this study can inform educators and policymakers about the potential of using mobile devices in online assessment practices, as an alternative to desktop computers. Originality/value: The study is novel, in that it provides quantitative evidence for the usability and user experience of both desktop computers and mobile devices when used in a summative assessment in the context of a higher education course. Study findings can contribute towards the interchangeable usage of desktop computers and mobile devices in assessment practices in higher education.